Apolipoprotein E isoform-dependent dendritic recovery of hippocampal neurons following activation of innate immunity - Maezawa, Izumi; Zaja-Milatovic, Snjezana; Milatovic, Dejan; Stephen, Christina; Sokal, Izabela; Maedo, Nobuyo; Montine, Thomas J.; Montine, Kathleen S. (My University, 2010)
Background: Innate immune activation, including a role for cluster of differentiation 14/toll-like receptor 4 coreceptors (CD14/TLR-4) co-receptors, has been implicated in paracrine damage to neurons in several neurodegenerative diseases that also display stratification of risk or clinical outcome with the common alleles of the apolipoprotein E gene (APOE): APOE2, APOE3, and APOE4. Previously, we have shown that specific stimulation of CD14/TLR-4 with lipopolysaccharide (LPS) leads to greatest innate immune response by primary microglial cultures from targeted replacement (TR) APOE4 mice and greatest p38MAPK-dependent paracrine damage to neurons in mixed primary cultures and hippocampal slice cultures derived from TR APOE4 mice. In contrast, TR APOE2 astrocytes had the highest NF-kappaB activity and no neurotoxicity. Here we tested the hypothesis that direct activation of CD14/TLR-4 in vivo would yield different amounts of paracrine damage to hippocampal sector CA1 pyramidal neurons in TR APOE mice. Methods: We measured in vivo changes in dendrite length in hippocampal CA1 neurons using Golgi staining and determined hippocampal apoE levels by Western blot. Neurite outgrowth of cultured primary neurons in response to astrocyte conditioned medium was assessed by measuring neuron length and branch number. Results: Our results showed that TR APOE4 mice had slightly but significantly shorter dendrites at 6 weeks of age. Following exposure to intracerebroventricular LPS, there was comparable loss of dendrite length at 24 hr among the three TR APOE mice. Recovery of dendrite length over the next 48 hr was greater in TR APOE2 than TR APOE3 mice, while TR APOE4 mice had failure of dendrite regeneration. Cell culture experiments indicated that the enhanced neurotrophic effect of TR APOE2 was LDL related protein-dependent. Conclusion: The data indicate that the environment within TR APOE2 mouse hippocampus was most supportive of dendrite regeneration while that within TR APOE4 hippocampus failed to support dendrite regeneration in this model of reversible paracrine damage to neurons from innate immune activation, and suggest an explanation for the stratification of clinical outcome with APOE seen in several degenerative diseases or brain that are associated with activated innate immune response.